국내 혈장분획제제 안전관리 정책과 특성에 대한 고찰 - 김지연(Ji Yeon Kim); 최민정(Min Joung Choi); 기성환(Sung Hwan Ki); 이원재(Wonjae Lee) (Yaghag-hoi-ji, 2022)
Plasma-derived medicinal products (PDMPs) are pharmaceuticals prepared using proteins in plasma, a liquidcomponent of blood. Regarding the use of human blood as a raw material in PDMP manufacturing, it has uniquecharacteristics unlike other pharmaceuticals (for example, limitations of scientific identification, finiteness of blood, and riskof infection through disease pathogens, such as the human immunodeficiency virus, hepatitis B virus, and hepatitis C virusin the blood). The safety management policy of PDMPs in Korea started with the enactment of the Blood ManagementAct in 1970. After that, the current safety management system was established through product approval managementaccording to the Pharmaceutical Affairs Act in 2006, higher standards of safety management for imported source plasmain 2009, and expansion of management standards for source plasma in 2012. The safety management of PDMPs involvesseveral important policies. Public management has been carried out by the Korean Red Cross and national government,and domestic plasma should be used first, while imported plasma may be used only if there is not enough. Additionally,to ensure blood products safety, plasma testing, inventory hold, and plasma master file reporting obligations are beingimplemented. In addition, it is managed as a subject of national lot release, which should also be quality-confirmed bythe country. Because the supply of domestic source plasma, which is the raw material of PDMPs, has shown a decreasingtrend in recent years, continuous monitoring and preparation is required. In this study, we describe the history of safetymanagement policies, including the definition and classification of PDMPs, product status, usage status of source plasma,and the related policy guidelines and characteristics. KCI Citation Count: 0